2015
DOI: 10.1002/jcsm.12040
|View full text |Cite
|
Sign up to set email alerts
|

Degenerin channel activation causes caspase-mediated protein degradation and mitochondrial dysfunction in adultC. elegansmuscle

Abstract: BackgroundDeclines in skeletal muscle structure and function are found in various clinical populations, but the intramuscular proteolytic pathways that govern declines in these individuals remain relatively poorly understood. The nematode Caenorhabditis elegans has been developed into a model for identifying and understanding these pathways. Recently, it was reported that UNC‐105/degenerin channel activation produced muscle protein degradation via an unknown mechanism.MethodsGeneration of transgenic and double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…4B ) confirming that CED-3 plays an important role in dystrophin-dependent muscle degeneration. Interestingly, degenerin-dependent muscle degeneration in C. elegans also depends on CED-3 74 . All the RNAi against executors of cell death tested provoked a decrease in the number of abnormal muscle in dys-1(cx18);hlh-1(cc561ts) mutant worms ( dys-1(cx18);hlh-1(cc561ts) mutant worms fed with: cps-6 RNAi: 5,01 +/− 0,32 abnormal muscle cells; wah-1 RNAi: 5,00 +/− 0,37 abnormal muscle cells; crn-2 RNAi: 4,81+/0,19 abnormal muscle cells; nuc-1 RNAi: 6,25 +/− 0,25 abnormal muscle cells; crn-6 RNAi: 6,53 +/− 0,26 abnormal muscle cells; ced-1 RNAi: 5,50 +/− 0,29 abnormal muscle cells; psr-1 RNAi: 5,31 +/− 0,24 abnormal muscle cells vs dys-1(cx18);hlh-1(cc561ts) mutant worms fed with the empty vector L4440: 9,63 +/− 0,24 abnormal muscle cells) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4B ) confirming that CED-3 plays an important role in dystrophin-dependent muscle degeneration. Interestingly, degenerin-dependent muscle degeneration in C. elegans also depends on CED-3 74 . All the RNAi against executors of cell death tested provoked a decrease in the number of abnormal muscle in dys-1(cx18);hlh-1(cc561ts) mutant worms ( dys-1(cx18);hlh-1(cc561ts) mutant worms fed with: cps-6 RNAi: 5,01 +/− 0,32 abnormal muscle cells; wah-1 RNAi: 5,00 +/− 0,37 abnormal muscle cells; crn-2 RNAi: 4,81+/0,19 abnormal muscle cells; nuc-1 RNAi: 6,25 +/− 0,25 abnormal muscle cells; crn-6 RNAi: 6,53 +/− 0,26 abnormal muscle cells; ced-1 RNAi: 5,50 +/− 0,29 abnormal muscle cells; psr-1 RNAi: 5,31 +/− 0,24 abnormal muscle cells vs dys-1(cx18);hlh-1(cc561ts) mutant worms fed with the empty vector L4440: 9,63 +/− 0,24 abnormal muscle cells) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Far left (green): caspase activation is induced by mitochondrial dysfunction, which can be caused by loss of degenerin channel contact with collagen in the extracellular matrix. 19 Left (violet): degradation by calpains is regulated by integrin attachment to the basement membrane, 18 and a significant portion of the integrin adhesome appears to contribute to this regulation. 16 Middle (yellow): autophagic degradation is controlled by a balance of signal from insulin/insulin-like receptor (negative regulator, green lines) and autocrine fibroblast growth factor signal (positive regulator, red lines).…”
Section: Figurementioning
confidence: 99%
“…20 Right (pink): intracellular calcium controlled by a combination of membrane depolarization, and G-protein signalling events are required to negatively regulate proteasome-based degradation. 15,17 Displayed model is adapted from models published in Shephard et al 17 and Gaffney et al 19 (B) A schematic of the full RNA interference screen can be found in the kinase screen 20 which this phosphatase screen is based upon. Briefly, for identification of phosphatase, genes whose knockdown induced autophagic protein degradation was achieved through four steps: (1) genes for which RNA interference produced decreased amounts of reporter protein in muscle were identified.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations